2011
DOI: 10.1007/s00415-011-6079-9
|View full text |Cite
|
Sign up to set email alerts
|

Neuropsychiatric symptoms and intelligence quotient in autosomal dominant Segawa disease

Abstract: Segawa disease is a rare dystonia due to autosomal dominant guanosine triphosphate cyclohydrolase I (adGTPCH) deficiency, affecting dopamine and serotonin biosynthesis. Recently, the clinical phenotype was expanded to include psychiatric manifestations, such as depression, anxiety, obsessive-compulsive disorder, and sleep disturbances. Although cognitive and neuropsychiatric symptoms may be attributable to dopamine deficiency in the prefrontal cortex and frontostriatal circuitry, intelligence is considered nor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
25
0
4

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 33 publications
(32 citation statements)
references
References 29 publications
3
25
0
4
Order By: Relevance
“…48 Intelligence is usually considered to be unimpaired in patients with GTP-CH-I deficiency, but one study showed that 64% of patients with the condition had IQ scores significantly below average (interquartile range , and were classed as having borderline intellectual functioning. 49 Autopsies have thus far provided no evidence of degeneration in the striatum or substantia nigra in patients with the classic presentation of DRD with GTP-CH-I deficiency. 50,51 However, dopamine levels were reduced in the nigrostriatal terminals (92% reduction in the putamen and 82% reduction in the caudate) relative to healthy control levels, but were preserved in the pars compacta of the substantia nigra.…”
Section: Introductionmentioning
confidence: 98%
“…48 Intelligence is usually considered to be unimpaired in patients with GTP-CH-I deficiency, but one study showed that 64% of patients with the condition had IQ scores significantly below average (interquartile range , and were classed as having borderline intellectual functioning. 49 Autopsies have thus far provided no evidence of degeneration in the striatum or substantia nigra in patients with the classic presentation of DRD with GTP-CH-I deficiency. 50,51 However, dopamine levels were reduced in the nigrostriatal terminals (92% reduction in the putamen and 82% reduction in the caudate) relative to healthy control levels, but were preserved in the pars compacta of the substantia nigra.…”
Section: Introductionmentioning
confidence: 98%
“…The ethics committee of University Hospital Reina Sofía approved the study. The neuropsychiatric features of the index case and her mother were previously reported (Family B)[6], as was the phenylalanine loading in the index case (case 14) [7], although at the time of those reports no mutation had been identified. The index case was born to healthy parents and presented with congenital torticollis that resolved completely by one year of age with physical therapy.…”
Section: Case Reportsmentioning
confidence: 98%
“…Sleep disturbance was identified in two adults and two children. In the adults this took the form of chronic sleep insufficiency (insomnia (n ¼ 1) and insufficient rest (n ¼ 1)) and in children was manifested as sleepwalking [14].…”
Section: Gtp-cyclohydrolase Deficiency (Gch1 Mutations)mentioning
confidence: 99%
“…All individuals were receiving dopaminergic therapy at the time of assessment [13]. Two studies have sought to address psychiatric, cognitive and sleep disturbance symptoms [14,15]. The first examined 7 adults and 7 children.…”
Section: Gtp-cyclohydrolase Deficiency (Gch1 Mutations)mentioning
confidence: 99%